Potential Cholesterol-lowering and Antihypertensive Effects of Cinnamon Tea: A Single Case Study - Nawaz , Mohammed; Murugesan, Sivanandhini; Devi, Gayathri; Mariappan, Saravanan; K, Maheshkumar (International Research Journal of Ayurveda & Yoga, 2024)
Hypercholesterolemia is a chronic cardiovascular condition characterized by high levels of cholesterol in the blood. Untreated hypercholesterolemia raises the risk of cardiovascular problems, necessitating effective treatment approaches. This single-case study evaluates the efficacy of cinnamon tea for a 52-year-old married man with high blood cholesterol (total cholesterol, triglycerides, low-density lipoprotein (LDL), and very-LDL. The patient presented with a history of head pain, elevated blood pressure (160/100 mmHg), and elevated blood triglyceride levels (232.6 mg/dL), diagnosed with hypertension and hypercholesterolemia. The patient was advised to consume a regular diet along with cinnamon tea for 2 months at the outpatient department of Sivaraj Naturopathy and Yoga Medical College and Hospital, Salem. Post-intervention assessments showed favorable outcomes, with a 70% symptomatic relief and a reduction in blood pressure from 160/100 mmHg to 140/90 mmHg. Notably, blood triglyceride levels decreased from 232.6 mg/dL to 176.4 mg/dL within 2 months. No serious adverse events were recorded. This single case study reports the effectiveness of cinnamon tea in a patient with hypertension and hypercholesterolemia. The naturopathic diet with cinnamon tea demonstrated remarkable effects and changes in the recorded data. However, further large-scale studies with improved designs are needed to validate these findings. Hypercholesterolemia, characterized by elevated levels of cholesterol in the blood, is a major risk factor for cardiovascular diseases such as atherosclerosis, heart attacks, and strokes.[1] High cholesterol can be caused by factors such as unhealthy diet, obesity, lack of physical activity, smoking, diabetes, and genetic predisposition.[2] Conventional treatments for hypercholesterolemia include lipid-lowering medications such as statins, fibrates, bile acid sequestrants, and lifestyle modifications such as dietary changes and increased physical activity.[3] However, these treatments may have side effects or be ineffective in some cases, prompting the need to explore complementary and alternative therapies.